STRATEGIES TO INCREASE STUDENTS 'ENTREPRENEURIAL INTEREST THROUGH CLASSROOM LEARNING, MSME OBSERVATION, ENTERPRISE PRACTICES, AND MENTORING - Cahyani, Putri Dwi; Cahya, Agus Dwi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to increase students' entrepreneurial interest through classroom learning, observation of small and medium enterprises (SMEs), entrepreneurial practices, and mentoring. Methodology approach using purposive random sampling, a total of 160 students who have received entrepreneurship learning at the Sarjanawiyata Tamansiswa University Yogyakarta. In this study, the analysis was carried out using descriptive analysis methods and inferential analysis methods Partial Least Square (PLS), namely variance-based SEM, with SmartPLS 3.0 software. Entrepreneurial learning positive and significant effect on the interests of students to entrepreneurship, Observasi to entrepreneurs (SMEs) positive effect on the interest of students to entrepreneurship, entrepreneurship practice positively affects student interest in entrepreneurship and mentoring does not have a positive effect on student interest in entrepreneurship